Swarna Sheetal: Cucumber variety for kharif season: - A, Sable P; Saras, Piyush Kumar; Mistry, J J (Indian Horticulture, 2023)
Cucumber is a very popular cucurbitaceous vegetable crop grown in kharif as well as spring (summer) season. Its tender fruit has a good taste and cooling effect. As a kharif season crop, it is sown in June end to July-August. This article discusses the variety Cucumber cv. Swarna Sheetal which responds to training system in kharif season. Trellis or bower system of training is preferred to facilitate intercultural operation, to obtain high yield and disease free crop.